Efek Terapi Kombinasi Postural Drainage dan Active Cycle of Breathing Technique Pada Pasien Tuberkulosis Paru - Aip Rukmana; Fitrian Rayasari; Dewi Anggraini (Universitas Malahayati, 2026)
ABSTRACT Pulmonary tuberculosis (TB) frequently causes impaired airway clearance due to increased mucus production and ineffective mucociliary function, leading to respiratory symptoms and reduced oxygenation. Postural Drainage (PD) and the Active Cycle of Breathing Technique (ACBT) are airway-clearance interventions proven to enhance secretion mobilization and improve pulmonary function. To determine the effect of combined PD and ACBT therapy on oxygen saturation, sputum volume, and cough–sputum symptoms in patients with pulmonary tuberculosis. This study used a quasi-experimental design with a pre–post test without control group involving 15 TB pulmonary patients recruited through purposive sampling. The intervention consisted of three sessions of combined PD and ACBT. Outcome measures included oxygen saturation (SpO₂), sputum volume, and CASA-Q scores. Data were analyzed using the paired t-test. The combination therapy significantly increased SpO₂ (96.07% to 98.00%; p = 0.001), sputum volume (2.87 mL to 5.40 mL; p = 0.000), and all CASA-Q domains related to cough and sputum (p = 0.000). Combined PD and ACBT therapy is effective in improving airway clearance, respiratory symptoms, and oxygenation in pulmonary TB patients. This intervention can be recommended as a safe, low-cost, and practical non-pharmacological therapy in respiratory nursing care. Keywords: Active Cycle of Breathing Technique, Airway Clearance, Postural Drainage, Pulmonary Tuberculosis. ABSTRAK Tuberkulosis paru sering menimbulkan gangguan bersihan jalan napas akibat peningkatan produksi mukus dan disfungsi mukosilier, sehingga memicu gejala respirasi dan penurunan oksigenasi. Postural Drainage (PD) dan Active Cycle of Breathing Technique (ACBT) merupakan intervensi pembersihan jalan napas yang terbukti meningkatkan mobilisasi sekret serta fungsi paru. Mengetahui efek terapi kombinasi PD dan ACBT terhadap saturasi oksigen, jumlah sputum, serta gejala batuk dan sputum pada pasien tuberkulosis paru. Penelitian menggunakan desain quasi-eksperimen pre–post test tanpa kelompok kontrol pada 15 pasien TB paru yang dipilih secara purposive. Intervensi diberikan dalam tiga sesi. Pengukuran mencakup SpO₂, volume sputum, dan skor CASA-Q. Analisis data menggunakan paired t-test. Terapi kombinasi memberikan peningkatan signifikan pada saturasi oksigen (96,07% menjadi 98,00%; p = 0,001), jumlah sputum (2,87 mL menjadi 5,40 mL; p = 0,000), serta seluruh domain batuk dan sputum pada CASA-Q (p = 0,000). Kombinasi PD dan ACBT efektif meningkatkan bersihan jalan napas, memperbaiki gejala respirasi, dan meningkatkan oksigenasi pada pasien TB paru. Intervensi ini dapat direkomendasikan sebagai terapi nonfarmakologis yang aman, mudah diterapkan, dan mendukung praktik keperawatan respirasi. Kata Kunci: Active Cycle of Breathing Technique, Bersihan Jalan Napas, Postural Drainage, Tuberkulosis Paru.